Statistical evaluation of the production of urea fertilizer multiwalled carbon nanotubes using plackett burman experimental design - Yatima, Norazlina Mohamad; Shaaban, Azizah; Dimina , Mohd Fairuz; Yusof, Faridah (Elsevier, 2015)
Plant growth rate is significantly dependent on application of nitrogenous fertilizer which mainly contributed by urea fertilizer (UF). Nanotechnology advancements in nutrition strategies for plants have attempted to assist plant nutrition for efficient plant growth. The development of carbon nanomaterials (NMs) including Multi-walled carbon nanotubes (MWNTs) in conjunction with the advancement in biotechnology has expanded their application area of in the field of agriculture. The aim of the work is to identify the significant process parameters to attach urea fertilizer (UF) onto MWNTs. The UF-MWNTs was than characterized optically and chemically to confirm their bonding. Comparison study was also conducted between UF-MWNTs and UF-functionalized MWNTs on total N content bonding to the MWNTs. The surface functional groups produced from functionalization process are essential for further modification of MWNTs and facilitate the separation of nanotube bundles into individual tubes. Optical, vibrational spectroscopy and chemical characterization were conducted on the samples using TEM, FTIR and total N analysis confirmed the successful bonding of urea onto MWNTs. Plackett-Burman Experimental Design showed, two out of nine investigated parameters (amount of functionalized MWNTs and percentage of functionalization) were found significant in producing successful attachment of UF onto functionalized MWNTs (fMWNTs).